Posterior fossa volume in idiopathic intracranial hypertension: a magnetic resonance imaging–based study. (January 2023) - Milarachi, Emily N; Gourishetti, Saikrishna C; Ciriello, Jonathan; Eisenman, David J; Raghavan, Prashant
Background: The etiology of idiopathic intracranial hypertension (IIH) is uncertain. Studies suggest the fundamental cause of the Chiari 1 malformation, a congenitally hypoplastic posterior fossa, may explain the genesis of IIH in some patients. Purpose: To assess the hypothesis that linear and volumetric measurements of the posterior fossa (PF) can be used as predictors of IIH. Material and Methods: A retrospective analysis of magnetic resonance imaging (MRI) studies on 27 patients with IIH and 14 matched controls was performed. A volumetric sagittal magnetization prepared rapid acquisition gradient echo sequence was used to derive 10 linear cephalometric measurements. Total intracranial and bony posterior fossa volumes (PFVs) were derived by manual segmentation. The ratio of PFV to total intracranial volume was calculated. Results: In total, 41 participants were included, all women. Participants with IIH had higher median body mass index (BMI). No significant differences in linear cephalometric measurements, total intracranial volumes, and PFVs between the groups were identified. Linear measurements were not predictive of volumetric measurements. However, on multivariate logistic regression analysis, the likelihood of IIH decreased significantly per unit increase in relative PFV (odds ratio [OR]=3.66 × 10 −50 ; 95% confidence interval [CI]=1.39 × 10 −108 to 1.22 × 10 −5 ; P = 0.04). Conversely, the likelihood of IIH increased per unit BMI increase (OR=1.19; 95% CI=1.04–1.47; P = 0.02). Conclusion: MRI-based volumetric measurements imply that PF alterations may be partly responsible for the development of IIH and Chiari 1 malformations. Symptoms of IIH may arise due to an interplay between these and metabolic, hormonal, or other factors.